Community Awareness and Delay in Diagnosis of Pulmonary Tuberculosis - Samar Abbas Jaffri, Maryam Mumtaz, Ata ur Rehman, Haya Fazal Maula, Kiran Khan, Saleha Afridi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pulmonary TB is a significant health issue amongst the developing nations. Early detection and timely intervention are necessary to manage transmission and enhance patient outcomes. Nonetheless, inadequate community awareness and delays in seeking medical services usually result in late diagnosis of the illness. Objective: To assess community awareness and its association with delay in the diagnosis of pulmonary tuberculosis. Methodology: This is a cross-sectional research carried out in the period between March 2023 and August 2023 at Department of Internal Medicine, Liaquat National Hospital, Karachi. Eighty-two patients with a diagnosis of pulmonary tuberculosis were used through a consecutive sampling method. The questionnaire used to collect data contained structured questions that captured the demographic, knowledge about tuberculosis, health seeking behaviour, and the period between the development of the symptoms and their diagnosis. Diagnostic delay was determined as 30 days or below or >30 days. Issues were analyzed with the help of SPSS 26. The Chi-square test was used to determine the relationship between awareness level and diagnostic delay with a p-value of 0.05 being a statistically significant value. Results: Among the 82 participants, 59.8% were male and 62.2% resided in rural areas. Overall awareness regarding tuberculosis was poor in 59.8% of participants. A total of 64.6% of patients experienced diagnostic delay greater than 30 days. Patients with poor awareness were significantly more likely to experience delayed diagnosis compared with those with good awareness (p = 0.002). Conclusion: Community awareness regarding pulmonary tuberculosis was limited and diagnostic delay was common among patients. Poor awareness was significantly associated with delayed diagnosis. Strengthening public health education and community awareness programs may help promote early health-seeking behavior and reduce diagnostic delay. Keywords: Pulmonary tuberculosis, community awareness, diagnostic delay, health-seeking behavior, tuberculosis control.